Understanding the Role of Yb3+ in the Nd/Yb Coupled 808-nm-Responsive Upconversion - Song, Nan; Zhou, Bo; Yan, Long; Huang, Jinshu; Zhang, Qinyuan (Frontiers in Chemistry, 2019)
The realization of upconversion at 808 nm excitation has shown great advantages in advancing the broad bioapplications of lanthanide-doped nanomaterials. In such a 808 nm responsive system Nd3+ and Yb3+ are both needed where Nd3+ acts as a sensitizer through absorbing the excitation irradiation, however, few work has been devoted to the role of Yb3+. Here, we report a systemic investigation on the role of Yb3+ by designing a set of core-shell-based nanostructures. We find that energy migration over the ytterbium sublattice plays a key role in facilitating the energy transportation, and moreover, we show that the interfacial energy transfer occurring at the core-shell interface also has a contribution to the upconversion. By optimizing the dopant concentration and surface anchoring the infrared indocyanine green dye, the 808 nm responsive upconversion is markedly enhanced. These results present an in-depth understanding on the fundamental interactions among lanthanides, and more importantly, they offer new possibilities to tune and control the upconversion of lanthanide-based luminescent materials.